Anaphylaxis in pediatric age: an overview - Marques, Maria Luís (2020)
Anaphylaxis is defined as an acute severe, life-threatening hypersensitivity reaction. The condition’s real prevalence and incidence are difficult to estimate, but seem to be increasing, particularly in children. Anaphylaxis clinical presentation varies according to age and other individual factors. Although consensual clinical criteria exist, including in pediatric age, diagnosis can be challenging. Food allergy is the most common anaphylaxis cause in children, particularly in preschool age. Drug-induced reactions and hymenoptera venom sting are other major triggers, which importance increases after adolescence. Management involves diagnosis, appropriate identification of possible triggers, acute phase treatment, and long-term planning. Prompt referral to a Pediatric Allergy specialist is recommended, as complete allergy workup is usually required to implement future preventive measures. In this review, the authors discuss particular aspects regarding anaphylaxis in pediatric age to provide information that can help improve disease management.